Using structured decision‐making to set restoration objectives when multiple values and preferences exist. Issue 6 (3rd October 2017) - Guerrero, Angela M.; Shoo, Luke; Iacona, Gwenllian; Standish, Rachel J.; Catterall, Carla P.; Rumpff, Libby; de Bie, Kelly; White, Zoe; Matzek, Virginia; Wilson, Kerrie A.
Abstract : Achieving global targets for restoring native vegetation cover requires restoration projects to identify and work toward common management objectives. This is made challenging by the different values held by concerned stakeholders, which are not often accounted for. Additionally, restoration is time‐dependent and yet there is often little explicit acknowledgment of the time frames required to achieve outcomes. Here, we argue that explicitly incorporating value and time considerations into stated objectives would help to achieve restoration goals. We reviewed the peer‐reviewed literature on restoration of terrestrial vegetation and found that while there is guidance on how to identify and account for stakeholder values and time considerations, there is little evidence these are being incorporated into decision‐making processes. In this article, we explore how a combination of stakeholder surveys and workshops can be used within a structured decision‐making framework to facilitate the integration of diverse stakeholder values and time frame considerations to set restoration objectives. We demonstrate this approach with a case of restoration decision‐making at a regional scale (southeast Queensland, Australia) with a view to this experience supporting similar restoration projects elsewhere.